Hot Deformation Behavior and Microstructural Evolution of AA 7050 Alloy under Plane Strain Compression - Yang, Qunying; Liu, Guodong; Liu, Xiaoyong (MATERIALS TRANSACTIONS, 2025)
The deformation behavior, processing maps and microstructure evolution of AA7050 aluminum alloy were investigated using plane strain compression at temperatures of 300~450 °C and various strain rates ranging from 0.01 to 10 s-1. Based on the flow stress and processing maps, the optimum hot working domains were established in the temperatures range of 420~450 °C and strain rates from 0.01 to 0.06 s-1. The microstructure characterization of the deformed sample with the maximal power dissipation efficiency indicated that the deformation mechanism is the combined effect of continuous dynamic recrystallization (CDRX) and discontinuous dynamic recrystallization (DDRX). At low strain, dynamic recrystallization (DRX) nucleation start preferentially at triple junctions. With increasing strain, continuous dynamic recrystallization grains are developed by the progressive rotation of sub-grains and the transformation from low angle boundaries to high angle boundaries within deformed grains. At the same time, discontinuous dynamic recrystallization grains spread along grain boundaries, which is related to the local grain boundary bulging. [doi: 10.2320/matertrans.MT-M2024173]